LRRK2 Phosphorylation, More Than an Epiphenomenon - Marchand, Antoine; Drouyer, Matthieu; Sarchione, Alessia; Chartier-Harlin, Marie-Christine; Taymans, Jean-Marc (Frontiers in Neuroscience, 2020)
Mutations in the Leucine Rich Repeat Kinase 2 gene (LRRK2) are linked to autosomal dominant Parkinson’s disease (PD) and genetic variation at the LRRK2 locus is associated with an increased risk for sporadic PD. This gene encodes a multiphosphorylated protein, including clusters of both heterologous phosphorylation and autophosphorylation sites. Several pieces of evidence indicate that LRRK2’s phosphorylation is important for its pathological and physiological functioning. These include a reduced LRRK2 heterologous phosphorylation in PD brains or after pharmacological inhibition of LRRK2 kinase activity as well as the appearance of subcellular LRRK2 accumulations when this protein is dephosphorylated at heterologous phosphosites. Nevertheless, the regulatory mechanisms governing LRRK2 phosphorylation levels and the cellular consequences of changes in LRRK2 phosphorylation remain incompletely understood. In this review, we present current knowledge on LRRK2 phosphorylation, LRRK2 phosphoregulation and how LRRK2 phosphorylation changes affect cellular processes that may ultimately be linked to disease mechanisms.